Second- Year Students’ Perceptions while using Google Classroom in Writing Descriptive Text at English Education Department of Universitas Negeri Padang - Devi Salmiati; Edi Trisno (Universitas Negeri Padang, 2023)
The purpose of this research was to describe the second-year students’ perception while using Google Classroom in writing descriptive text. The descriptive method was used as the design of this research. The population of this research was the second-year students at English Education Department of Universitas Negeri Padang. The researcher used a simple random ampling technique to select the sample, and the number sample was 40 students. The instrument for collecting the data in this research was a questionnaire. The researcher used Microsoft excel 2016 to analyze the data. After analyzing the data, the researcher found that most second-year students' perception while using google classroom in writing descriptive text was had positive perception. The result in this study indicated that the second year students of English Education Department of universitas negeri padang especially in paragraph writing class had positive perceptions while using Google Classroom in learning about writing descriptive text. To conclude that the second year students at english education department of universitas negeri padang especially in paragraph writing class have positive perception while using google classroom in learning about writing descriptive text and also Google Classroom can be use for media of online learning in writing descriptive text